2009
DOI: 10.1103/physreva.80.042108
|View full text |Cite
|
Sign up to set email alerts
|

Quantum decoherence of two qubits

Abstract: It is commonly stated that decoherence in open quantum systems is due to growing entanglement with an environment. In practice, however, surprisingly often decoherence may equally well be described by random unitary dynamics without invoking a quantum environment at all. For a single qubit, for instance, pure decoherence (or phase damping) is always of random unitary type. Here, we construct a simple example of true quantum decoherence of two qubits: we present a feasible phase damping channel of which we show… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
76
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 37 publications
0
76
0
Order By: Relevance
“…This behavior explains the observed buildup of the quasi-equilibrium in liquid crystals. The results of this work, together with the conclusions obtained in references 11,13 , can contribute to elucidate the underlying quantum mechanisms for decoherence of open quantum systems of interacting spins, for instance the role played by quantum correlations between the observed system and the environment in the damping of the spin coherences 25,26 . Certainly, these works showed that in liquid crystals it is essential to assume the quantum character of the spin-environment coupling to explain the observed irreversible decoherence.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…This behavior explains the observed buildup of the quasi-equilibrium in liquid crystals. The results of this work, together with the conclusions obtained in references 11,13 , can contribute to elucidate the underlying quantum mechanisms for decoherence of open quantum systems of interacting spins, for instance the role played by quantum correlations between the observed system and the environment in the damping of the spin coherences 25,26 . Certainly, these works showed that in liquid crystals it is essential to assume the quantum character of the spin-environment coupling to explain the observed irreversible decoherence.…”
Section: Discussionmentioning
confidence: 60%
“…Also, understanding the nature of the decoherence mechanism can contribute to the set up of a quantum spin-lattice relaxation theory beyond the Markovian limit, providing insight into the interplay of the quantum correlations developed in the microscopic irreversible dynamics and the dissipative macroscopic evolution. Finally, the analysis carried out in this work may contribute to the current discussion about the role of system-environment entanglement as basic mechanism of quantum decoherence of interacting particle systems 1,[25][26][27] .…”
Section: Introductionmentioning
confidence: 90%
“…The reduced dynamics can be obtained from a local Schrödinger equation driven by a random Hermitian Hamiltonian. By contrast, genuine quantum decoherence may be found in two-qubit systems [28]. It is also worth noting that random unitary dynamics emerging from an open quantum system with environmental initial pure state can always be "undone"(quantum error correction) [41,42].…”
Section: Random Unitary Representationsmentioning
confidence: 99%
“…So even for larger Hilbert space dimension than two -on a local level -pure dephasing based on a quantum oscillator model like (1) cannot be distinguished from random unitary dynamics. For genuine quantum decoherence, one needs "more quantum mechanical" environments [28].…”
Section: Random Unitary Representationsmentioning
confidence: 99%
“…In these situations, classical stochastic modeling of the environment represents a valid and reliable alternative. In fact, it has been shown that for certain system-environment interactions a classical description can be found that is completely equivalent to the quantum description [63][64][65][66][67][68]. In addition, there is experimental evidence that many quantum systems of interest interact with classical forms of noise, typically Gaussian noise [69][70][71].…”
Section: Introductionmentioning
confidence: 99%